2003
DOI: 10.1207/s15374424jccp3201_07
|View full text |Cite
|
Sign up to set email alerts
|

Callous-Unemotional Traits, Impulsivity, and Emotional Processing in Adolescents With Antisocial Behavior Problems

Abstract: Examined the emotional reactivity of adolescents with antisocial behavior problems using a lexical decision paradigm. Evidence from adult forensic samples indicates that psychopathic traits are associated with abnormalities in the processing of emotional stimuli. In an attempt to extend these findings earlier in development, this association was tested in a sample of adolescents (mean age = 16.01; SD = 1.32) referred to a diversion program for delinquent behavior. Emotional processing was assessed by comparing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
117
1
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 275 publications
(130 citation statements)
references
References 68 publications
8
117
1
2
Order By: Relevance
“…The subgrouping of children on the basis of CU traits might explain inconsistencies of past investigations with respect to empathy related deficits in CD children. Present findings, considered together with research on emotion processing that has shown decreased orienting to negative emotional stimuli in CD/CU children, and increased orienting to negative emotional stimuli in CD-only children [37,38], suggest substantial differences in emotion related processing and responsiveness (particularly of negative emotions and perhaps differentiated patterns across different negative emotions) across CD/CU and CD-only subgroups that warrant further detailed investigation. Present physiological data for CD/CU children support theories linking failure to inhibit antisocial conduct to an early dysfunction in the capacity for vicarious affective arousal, as proposed by Hoffman [6], and a consequent failure to develop a 'Violence Inhibition Mechanism', as proposed by Blair [58].…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…The subgrouping of children on the basis of CU traits might explain inconsistencies of past investigations with respect to empathy related deficits in CD children. Present findings, considered together with research on emotion processing that has shown decreased orienting to negative emotional stimuli in CD/CU children, and increased orienting to negative emotional stimuli in CD-only children [37,38], suggest substantial differences in emotion related processing and responsiveness (particularly of negative emotions and perhaps differentiated patterns across different negative emotions) across CD/CU and CD-only subgroups that warrant further detailed investigation. Present physiological data for CD/CU children support theories linking failure to inhibit antisocial conduct to an early dysfunction in the capacity for vicarious affective arousal, as proposed by Hoffman [6], and a consequent failure to develop a 'Violence Inhibition Mechanism', as proposed by Blair [58].…”
Section: Discussionsupporting
confidence: 50%
“…CD/CU children have shown substantial evidence of affect-related deficits such as decreased orienting to affective stimuli [37,38], and insensitivity to distress cues [35,39]. CD/CU children have further shown high levels of thrill and adventure-seeking (i.e.…”
mentioning
confidence: 99%
“…DOI: 10.1002/ab.20224 Farrington, 2005]. CU traits have been shown to play an important role in understanding CPs in children across a wide variety of areas, including social cognition [Pardini et al, 2003;Waschbusch et al, 2007], biological and neuropsychological characteristics Lynam, 1998], response to contingencies [Barry et al, 2000;Budhani and Blair, 2005;O'Brien and Frick, 1996;Vitale et al, 2005], style of parenting they experienced [Christian et al, 1997;Oxford et al, 2003;Wootton et al, 1997], anxiety and temperament [Barry et al, 2000;Frick and Morris, 2004], emotional processing [Blair et al, 2001;Loney et al, 2003], heritability of antisocial behavior [Taylor et al, 2003;Viding et al, 2005], personality structure [Lynam et al, 2005;, and type and severity of antisocial behavior [Frick et al, 2003a[Frick et al, ,b, 2005Lynam, 1997Lynam, , 1998]. As a whole this research strongly suggests that CU is an important factor to consider when examining CP in children [for a review, see Kotler and McMahon, 2005].…”
Section: Introductionmentioning
confidence: 99%
“…There is a growing body of evidence to support this hypothesis. Specifically, CU traits have been shown to influence the association between CP and biological and neuropsychological characteristics [7,8], response to contingencies [9,10], style of parenting they experienced [11,12], anxiety and temperament [6,13], emotional processing [14], heritability of antisocial behavior [15], and type and severity of antisocial behavior [7,[16][17][18][19]. This considerable body of evidence persuasively argues that CU traits play an important role in understanding CP in children.…”
Section: Introductionmentioning
confidence: 99%